Awareness and quality of knowledge regarding HIV/AIDS among women in India - Rimjhim M. Aggarwal Jeffrey J. Rous (Journal of Development Studies, Vol. 42, No. 3, 371 - 401, April 2006, 2006)
This paper examines the determinants of women's knowledge regarding HIV/AIDS using data from a nationally representative survey in India. Although around 45 per cent of sample women had heard about the disease, their knowledge regarding its modes of transmission and prevention is found to be limited. To explore the possibility that there may be a different process that determines awareness as opposed to quality of knowledge regarding HIV/AIDS, a negative binomial hurdle model and a two-stage ordered probit model are estimated. The results show that the effect of several covariates, such as education and mass media, on awareness is different from their effect on quality of knowledge.